2014
DOI: 10.1021/ie501280p
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Water Scrubbing Process and Energy Requirements for CO2 Capture to Upgrade Biogas to Biomethane

Abstract: Water scrubbing is the most widely used technology for removing CO 2 from biogas and landfill gas. This work developed a rate-based mass transfer model of the CO 2 -water system for upgrading biogas in a packed bed absorption column. The simulated results showed good agreement with both a pilot-scale plant operating at 10 bar, and a large-scale biogas upgrading plant operating at atmospheric pressure. The calculated energy requirement for the absorption column to upgrade biogas to 98% CH 4 (0.23 kW h N m 3 , o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 18 publications
1
28
0
2
Order By: Relevance
“…Finally, in Fig. 7 of [41] the results for a smaller plant (60 Nm 3 /h) are presented. It is shown that minimal power requirement is achieved at 0.8 MPa -0.32 kWh/Nm 3 raw biogas, which is roughly the same as our predictions.…”
Section: Overview Of Literature Datamentioning
confidence: 99%
“…Finally, in Fig. 7 of [41] the results for a smaller plant (60 Nm 3 /h) are presented. It is shown that minimal power requirement is achieved at 0.8 MPa -0.32 kWh/Nm 3 raw biogas, which is roughly the same as our predictions.…”
Section: Overview Of Literature Datamentioning
confidence: 99%
“…Three retrofits were used and tested separately using gas engine-First system which captures CO₂ from crude biogas by chemical absorption process Second system which captures CO₂ after combustion of biogas by chemical absorption process and third system which captures CO₂ after combustion of raw biogas with pure O₂ instead of air (oxy-fuel combustion process). Moreover, after the comparison we have found that first system provides the better results compare with the other two systems [11].…”
Section: Different Types Of Purification Methodsmentioning
confidence: 73%
“…Known as "water scrubbing," the higher solubility of CO 2 relative to CH 4 allows it to preferentially dissolve in water, effecting separation. The required energy input needed to produce 98 wt% CH 4 from biogas (containing ~50% CH 4 and ~50% CO 2 ) in a 10 bar pilot-scale plant has f = ~5% (Nock et al, 2014). Similarly, poly(ethylene glycol) has been used to remove CO 2 from biogas, and is estimated to require f = 7-9% to regenerate (Luostarinen et al, 2011).…”
Section: Differential Solubility To Separate Gas Mixturesmentioning
confidence: 99%